An open-path, hand-held laser system for the detection of methane gas - van Well, Ben; Murray, Stuart; Hodgkinson, Jane; Pride, Russ D.; Strzoda, Rainer; Gibson, Graham; Padgett, Miles (Institute of Physics (IOP), 2005)
We have developed an open-path hand-held gas detector incorporating a distributed feedback InGaAs laser diode at 1.65 µm. Incorporated into a hand-held transceiver unit, the emitted laser beam is backscattered from nearby surfaces, collected and focused onto an amplified InGaAs detector using a 150 mm diameter plastic Fresnel lens. At ranges of 4–5 m, a typical backscattered signal is tens of nanowatts of laser light. Applying second derivative wavelength modulation spectroscopy gives a sensitivity to methane of better than 10 parts per million over a one metre path length. A number of demonstration units have been fabricated and successfully evaluated by end users.
Keywords: methane; wavelength modulation spectroscopy; instrumentation; infrared spectroscopy; remote detection